The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.2147/cia.s413313
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Values of White Blood Cell Indices (Lymphocyte and Eosinophilic Granulocyte) for Heart Failure in Acute Coronary Syndrome Patients Following Percutaneous Coronary Intervention: A Prospective Cohort Study

Abstract: Background White blood cell (WBC) indices are strongly associated with cardiovascular disease, but data on the prognostic values of these parameters in patients with acute coronary syndrome (ACS) following percutaneous coronary intervention (PCI) are sparse. The current study aimed to investigate the relationship between baseline WBC indices levels and the incidence of heart failure (HF) in ACS patients after PCI and explore the predictive values over a 2-year follow-up period. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Our study demonstrated a statistically significant correlation between a high lymphocyteto-red blood cell ratio (LRR) value and an increased risk of developing Killip class III/IV. Previous studies support our results, demonstrating that a high lymphocyte count is correlated with an unfavorable prognosis [35].…”
Section: Lymphocytes-the Second Pillar Of the Bottom-up Phenomenonsupporting
confidence: 92%
“…Our study demonstrated a statistically significant correlation between a high lymphocyteto-red blood cell ratio (LRR) value and an increased risk of developing Killip class III/IV. Previous studies support our results, demonstrating that a high lymphocyte count is correlated with an unfavorable prognosis [35].…”
Section: Lymphocytes-the Second Pillar Of the Bottom-up Phenomenonsupporting
confidence: 92%
“…Heart failure (HF) is now one of the most common causes of cardiovascular disease, with increasing morbidity and mortality rates ( 1 ), and HF occurrence is closely related to the long-term survival of patients with acute coronary syndrome ( 2 ). Chronic HF (CHF) is a common complication of several heart diseases, characterized by impaired ventricular filling and ejection ( 3 ).…”
Section: Introductionmentioning
confidence: 99%